Seasonal species composition, abundance and public health importance of mosquito vectors (Diptera: Culicidae) in Huai Tha Khoei Reservoir, Ratchaburi, Thailand - TANAWAT CHAIPHONGPACHARA; SEDTHAPONG LAOJUNA (Society for Indonesian Biodiversity, 2024)
Abstract. Chaiphongpachara T, Laojuna S. 2024. Seasonal species composition, abundance and public health importance of mosquito vectors (Diptera: Culicidae) in Huai Tha Khoei Reservoir, Ratchaburi, Thailand. Biodiversitas 25: 1264-1275. Mosquitoes are vectors for pathogens that cause life-threatening diseases in humans and animals. Significant mosquito-borne diseases include malaria, dengue, chikungunya, Zika, Japanese encephalitis, and filariasis. Anthropogenic environmental changes can significantly impact the dynamics of disease vector populations, which can lead to outbreaks of mosquito-borne diseases. This study investigated the seasonal variation in species composition and abundance of mosquito vectors around the Huai Tha Khoei Reservoir in Ratchaburi Province, Thailand, across cool, hot, and rainy seasons. A total of 1363 mosquitoes, representing 30 species from five genera, were collected. In particular, 25 of these species, accounting for 83.33% of the total, were identified as vectors of human pathogens. The most dominant species across all seasons was Culex tritaeniorhynchus Giles 1901, representing 39.47% (n=538) of the total, followed by Anopheles barbirostris Wulp 1884 s.l. (14.38%, n = 196) and Culex vishnui Theobald 1901 (9.02%, n=123). The Shannon diversity index was highest during the rainy season (H’= 2.144) and lowest in the hot season (H’=1.788). This is consistent with the results of the UPGMA tree based on beta diversity, indicating that mosquito diversity in the rainy season differs significantly from that in the cool and hot seasons. The findings enhance our understanding of the impact of seasonality on mosquito vectors in this region, which is crucial for developing effective disease control strategies. Additionally, this study serves as a valuable reference for understanding the diversity of mosquito vectors in other areas.